Sediment Provenance in the Baker-Martínez Fjord System (Chile, 48°S) Indicated by Magnetic Susceptibility and Inorganic Geochemistry - Troch, Matthias; Bertrand, Sebastien; Amann, Benjamin; Liu, Dawei; Placencia, Juan A.; Lange, Carina B. (Frontiers in Marine Science, 2021)
Fjord sediments are increasingly used as high-resolution archives of climate and environmental change, including variations in glacier mass balance and terrestrial hydrology. To accurately interpret such sediment records, it is crucial to comprehend sediment transport processes and determine sediment provenance. With this in mind, our main objective is to identify cost-effective parameters that can be used to reconstruct relative variations in the origin of sediments deposited in the Baker-Martínez fjord system, which is located between the Northern (NPI) and Southern (SPI) Patagonian Icefields. We focus on estimating the proportions of sediment derived from each icefield, taking advantage of the clearly distinct lithologies that underlie NPI (Patagonian Batholith) and SPI (Eastern Andean Metamorphic Complex) glaciers. The magnetic susceptibility and inorganic geochemistry of 21 surface sediment samples collected along the fjord system and that of suspended sediment samples from the four main rivers that discharge at its heads were investigated. Results indicate that sediments derived from the NPI are characterized by higher magnetic susceptibility and log(Ti/Al) values than those from the SPI, reflecting the mafic nature of the batholith. In fjords that receive contributions from both the NPI and SPI, magnetic susceptibility and log(Ti/Al) primarily reflect sediment provenance. In fjords receiving sediment from only one icefield, however, these parameters are positively correlated with grain size and reflect the progressive settling of particles from the surficial plume. Our results suggest that magnetic susceptibility and log(Ti/Al) can be used to reconstruct sediment provenance within the Baker-Martínez fjord system, but that only log(Ti/Al) can provide quantitative estimates of the proportions of sediment derived from each icefield. Ultimately, applying these provenance indicators to long sediment cores from the Baker-Martínez fjord system could allow reconstructing relative variations in sediment input from each icefield, which may in turn be interpreted as changes in river discharge and/or glacier mass balance.